Inflammation on the Cervical Papanicolaou Smear: Evidence for Infection in Asymptomatic Women? - Stavroula Baka; Ioanna Tsirmpa; Anthia Chasiakou; Iliana Tsouma; Ekaterina Politi; Vassiliki Gennimata; Evangelia Kouskouni (Hindawi Limited, 2013)
Background. The significance of the possible presence of infection on the Pap smear of asymptomatic women based on cytological criteria is practically unknown. Materials and Methods. A total of 1117 asymptomatic nonpregnant women had Pap smear tests and vaginal as well as cervical cultures completed (622 with and 495 without inflammation on the Pap smear). Results. Out of the 622 women with inflammation on Pap test, 251 (40.4%) had negative cultures (normal flora present), while 371 (59.6%) women had positive cultures with different pathogens. In contrast, the group of women without inflammation on Pap test displayed significantly increased percentage of negative cultures (67.1%, ) and decreased percentage of positive cultures (32.9%, ). Bacterial vaginosis was diagnosed more frequently in both groups and significantly more in the group with inflammation on Pap smear compared to the group without inflammation (). Conclusions. A report of inflammatory changes on the cervical Pap smear cannot be used to reliably predict the presence of a genital tract infection, especially in asymptomatic women. Nevertheless, the isolation of different pathogens in about 60% of the women with inflammation on the Pap smear cannot be overlooked and must be regarded with concern.